Endoparasites of Arctic Wolves in Greenland - Marquard-Petersen, Ulf (ARCTIC, 1997)
Fecal flotation was used to evaluate the presence of intestinal parasites in 423 wolf feces from Nansen Land, North Greenland (82 55 N, 41 30 W) and Hold with Hope, East Greenland (73 40 N, 21 00 W), collected from 1991 to 1993. The species diversity of the endoparasitic fauna of wolves at this high latitude was depauperate relative to that at lower latitudes. Eggs and larvae of intestinal parasites were recorded in 60 feces (14%): Nematoda (roundworms) in 11%; Cestoda (flatworms of the family Taeniidae) in 3%. Four genera were recorded: Toxascaris, Uncinaria, Capillaria, and Nematodirus. Eggs of taeniids were not identifiable to genus, but likely represented Echinococcus granulosus and Taenia hydatigena. The high prevalence of nematode larvae may be a consequence of free-living species' invading the feces. The occurrence of taeniids likely reflects the reliance of wolves on muskoxen for primary prey. This is the first quantitative study of the endoparasites of wolves in the High Arctic. On a utilisé la flottation coproscopique afin d'évaluer la présence de parasites intestinaux dans 423 excréments de loups prélevés de 1991 à 1993 à Nansen Land dans le Groenland septentrional (82° 55' de latit. N., 41° 30' de latit. O.) et à Hold with Hope dans le Groenland oriental (73° 40' de latit. N, 21° 00' de latit. O.). La diversité des espèces de la faune endoparasite des loups à cette haute latitude était peu importante par rapport à celle de latitudes plus basses. On a noté la présence d'oeufs et de larves de parasites intestinaux dans 60 excréments (14 p. cent): nématodes (vers ronds) dans 11 p. cent; cestodes (vers plats de la famille du ténia) dans 3 p. cent. On a relevé 4 genres: Toxascaris, Uncinaria, Capillaria et Nematodirus. On n'a pas pu relier les oeufs de ténias à des genres, mais ils représentaient probablement Echinococcus granulosus et Taenia hydatigena. La fréquence élevée de larves de nématodes peut être une des conséquences d'espèces libres qui envahissent les excréments. La présence de taenidae ...